BOIKOT PRODUK ISRAEL DI INDONESIA BERDASARKAN PERJANJIAN YANG DILARANG DALAM UNDANG-UNDANG NO 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Darma Pratiwi, Agustina Ni Made Ayu; Lestari, Anak Agung Adi; Sukardi, Ni Made Rai (Jurnal Ilmiah Raad Kertha, 2024)
Boycotting business competition is one of the prohibited agreements. The close historical relationship between Indonesia and Palestine means that Indonesia continues to support Palestinian independence. One of the most prominent reactions to this conflict was the boycott of Israeli products. Companies such as Danone and Coca-Cola, Starbucks which are affected by the boycott must make it clear to the public that the boycott actions that have been carried out so far are not in the context of business competition and do not violate Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Competition. Unhealthy business but commitment to humanity. The call for a boycott is just fanaticism without a religious connection because companies that come to Indonesia only want to invest